The Review of Sexual Assault Cases Those Reflected to Adana Penalty Courts - Çekin, Necmi; Hilal, Ahmet; Bilgin, Nursel; Alper, Benhan; Gülmen, Mete Korkut; Savran, Bülent; Sarıca, Ayşe Dolunay (The Bulletin of Legal Medicine, 1998)
The victims of sexual assault cases seem to refuse the events and do not engage in legal ways to handle the situation. This study was designed to discuss the related laws in the criminal code law, in light of cases brought to the attention of the Criminal Court. The summaries of the court decisions of the Adana Penalty Court (1996/1-450 and 1997/1-150) were reviewed in order to group the age, sex and the claimed event together with the decisions made by the court. Of the 81 victims, only 3 were male. 55.55% of the victims were aged between 12-15, 37.03 % of the accused were between the ages 21 and 30. İn 22 cases, the victim and the accused got married and according to TCK 434 the court was dismissed. In 24 cases, the accused got free for several reasons and in 43-20% of the cases, the accused received punishment. The dilemma between the legal age for having sexual relationships and legal age of marriage and the postponement of the punishment in case of marriage suggests the need for sexual assault centers around the country.Key words: Penalty Courts, Sexual Assault, Marriage, Gender.
Keywords: penalty courts; sexual assault; marriage; gender